2022
DOI: 10.1093/nar/gkac1065
|View full text |Cite
|
Sign up to set email alerts
|

MobiDB: 10 years of intrinsically disordered proteins

Abstract: The MobiDB database (URL: https://mobidb.org/) is a knowledge base of intrinsically disordered proteins. MobiDB aggregates disorder annotations derived from the literature and from experimental evidence along with predictions for all known protein sequences. MobiDB generates new knowledge and captures the functional significance of disordered regions by processing and combining complementary sources of information. Since its first release 10 years ago, the MobiDB database has evolved in order to improve the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 56 publications
0
72
0
Order By: Relevance
“…We next focused on the N-terminal regions of ECT1/9/11 . Because protein disorder predictions using MobiDB (66) confirmed that they are all disordered (Fig. S11), we used approaches suitable for the study of IDRs.…”
Section: Resultsmentioning
confidence: 99%
“…We next focused on the N-terminal regions of ECT1/9/11 . Because protein disorder predictions using MobiDB (66) confirmed that they are all disordered (Fig. S11), we used approaches suitable for the study of IDRs.…”
Section: Resultsmentioning
confidence: 99%
“…The update from GPCRdb ( 27 ) reports state-specific AF2 models alongside other new features such as lists of ligands for each receptor, both endogenous and surrogate. Even MobiDB ( 28 ), focusing on intrinsically disordered proteins, benefits from two AF2-related predictions unforeseen by the original methods developers: predictions of disordered regions and potential interaction motifs contained within them. Other classes of proteins with special structural properties are covered by the new Amylograph ( 29 ) which curates information on amyloid-amyloid interactions and the returning PhaSepDB ( 30 ) for proteins that can participate in phase separation, now doubled in size and with much more detailed annotations.…”
Section: New and Updated Databasesmentioning
confidence: 99%
“…Several machine learning methods, from simple linear regression to more sophisticated approaches such as support vector machines and deep learning (artificial neural networks with multiple layers), can combine existing sequence descriptors to predict the disordered sequences. With the increasing degrees of freedom (sequence descriptors) and increasing training datasets (e.g., DisProt [ 108 ], IDEAL [ 109 ], MobiDB [ 110 ], and solved PDB structures), deep learning has become a commonly used method for this purpose. A recent assessment testing 43 predictors found that machine learning methods and specifically deep learning methods outperform physicochemical methods [ 111 ].…”
Section: Theoretical and Computational Biophysical Techniquesmentioning
confidence: 99%